Earnings Profile: Ability and Schooling: Comment - Weisbrod, Burton A. (Journal of Political Economy, 1972)
John Hause's paper is addressed to the perplexing matters of how to disentangle the effects of and schooling on worker earnings, and of the effect of on earnings over a worker's lifetime.' His emphasis oil ability and schooling as determinants of earnings is surely not intended to deny that other variables also affect earnings or to deny that these other variables may also interact with and schooling level-but he barely touches on other variables or the possibility of interactions.